Context-dependent compensation among phosphatidylserine-recognition receptors. Issue 1 (December 2017) - Penberthy, Kristen; Rival, Claudia; Shankman, Laura; Raymond, Michael; Zhang, Jianye; Perry, Justin; Lee, Chang; Han, Claudia; Onengut-Gumuscu, Suna; Palczewski, Krzysztof; Lysiak, Jeffrey; Ravichandran, Kodi
Abstract Phagocytes express multiple phosphatidylserine (PtdSer) receptors that recognize apoptotic cells. It is unknown whether these receptors are interchangeable or if they play unique roles during cell clearance. Loss of the PtdSer receptorMertk is associated with apoptotic corpse accumulation in the testes and degeneration of photoreceptors in the eye. Both phenotypes are linked to impaired phagocytosis by specialized phagocytes: Sertoli cells and the retinal pigmented epithelium (RPE). Here, we overexpressed the PtdSer receptor BAI1 in mice lacking MerTK (Mertk −/− Bai1 Tg ) to evaluate PtdSer receptor compensationin vivo . WhileBai1 overexpression rescues clearance of apoptotic germ cells in the testes ofMertk −/− mice it fails to enhance RPE phagocytosis or prevent photoreceptor degeneration. To determine why MerTK is critical to RPE function, we examined visual cycle intermediates and performed unbiased RNAseq analysis of RPE fromMertk +/+ andMertk −/− mice. Prior to the onset of photoreceptor degeneration, Mertk −/− mice had less accumulation of retinyl esters and dysregulation of a striking array of genes, including genes related to phagocytosis, metabolism, and retinal disease in humans. Collectively, these experiments establish that not all phagocytic receptors are functionally equal, and that compensation among specific engulfment receptors is context and tissue dependent.